Risk of Recurrence of Symptomatic Intracranial Atherosclerosis in Posterior Circulation Seen to Be Higher Than That in Anterior Circulation in Long-Term Follow-Up - Zhang, Jingyu; Zhang, Kai; Jia, Baixue; Qi, Zhongqi; Mo, Dapeng; Ma, Ning; Gao, Feng; Miao, Zhongrong (Frontiers in Neurology, 2020)
Background: Intracranial atherosclerotic stenosis (ICAS) is an important cause of ischemic stroke. In Asians, intracranial atherosclerotic disease leads to 33–50% of ischemic events. At present, treatment with medication vs. endovascular therapy (EVT) for symptomatic ICAS (sICAS) patients is still debatable. The clinical prognosis of patients who are not completely free of stroke symptoms despite regular medication and are not eligible for EVT for various reasons, is not yet investigated. Aim: To report the long-term recurrence rate of stroke in a cohort of symptomatic ICAS patients who intended to undergo EVT upon admission but could not for various reasons after digital subtraction angiography (DSA) evaluation. Method: This is a retrospective analysis of consecutive sICAS patients in a single center from January 1, 2016 to August 31, 2017 who underwent DSA assessment alone and were not eligible for further EVT. Demographic information, risk factors related to cerebrovascular disease, clinical comorbidities, medication, imaging data, and long-term outcomes were reported. Results: A total of 218 patients were included in the study; 42 (19.2%) patients had recurrence of stroke/transient ischemic attack (TIA) at the 1-year follow up. Patients were divided into two groups according to lesions in anterior circulation (n = 120) or posterior circulation (n = 98). There was a higher stroke/TIA recurrence rate in the posterior circulation than anterior circulation group (25.5 vs. 14.2%, p = 0.035). Given the advanced age, higher prevalence of coronary heart disease, larger stenosis length, and poorer collateral circulation, the posterior circulation group showed a higher risk of recurrent stroke/TIA and death than the anterior circulation group [HR = 3.092, 95% CI (1.335–7.164), p = 0.0084], after adjusting for all confounding factors in the COX regression model. Kaplan–Meier analysis showed that sICAS recurrence and mortality risk in the posterior circulation group was consistently higher than that in the anterior circulation group (log-rank-test, p = 0.033). Conclusions: Patients with posterior circulation sICAS have higher recurrence risk than those with anterior circulation managed with medication alone. Further, posterior circulation lesion is an independent risk factor for recurrence in sICAS patients.